Osnownyje naprawlenija politiki stimulirowanija priwleczenija inostrannych inwiesticij w ekonomiku Łatwii - Sieriogina, Ałła; Caurkubule, Żanna (The Main Directions of the Politics of the Promotion of Foreign Input in the Economics Of Latvia, 2007)
In the paper titled “The Main Directions of the Politics of the Promotion of Foreign Input in the Economics of Latvia”, the most important question of making investments in Latvia with the purpose of ensuring its further growth, and development of its economy, is considered and substantiated. In the work, the positive process of renovation of investment policy is emphasized, starting from 1996, and some data are provided regarding the projects for investments in the most important branches by the state sector. As study showed, the further growth of foreign investments is envisaged in the most attractive programmes and projects, which are expedient for implementation in the Republic of Latvia. The article contains the characterization of the main economic zones. Both the tendency of the development of free economic zones and their influence on the development of Latvian regions are analyzed. In the article the analysis of the problem of free economic zones development is carried out in the article. The suggestions about the development of free economic zones related with the entering Latvia in to the European Union are also given.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (15); 2007; nr 1166, s. 162-169